Maternal employment status and early initiation of breastfeeding in Indonesian urban areas - Lestari, Weny; Izza, Nailul; Kristiana, Lusi; Maryani, Herti; Andarwati, Pramita; Paramita, Astridya; Laksono, Agung Dwi (BKM Public Health and Community Medicine, 2025)
Purpose: The first human milk produced contains highly nutritious colostrum and antibodies that could protect newborns against disease. The study analysed the role of maternal employment status in achieving early initiation of breastfeeding in urban Indonesia. Methods: This cross-sectional study employed secondary data from the 2017 Indonesia Demographic and Health Survey. The study analyzed 36,163 women with children under 24 months old. The study used early initiation of breastfeeding as the outcome variable and maternal employment status as the exposure variable. Furthermore, the research employed ten control variables: maternal current marital status, age, education, parity, wealth, antenatal care, place of delivery, mode of delivery, type of birth, and child sex. The authors employed a binary logistic regression in the final test. Results: The study showed that unemployed mothers were 1.587 times more likely to experience early initiation of breastfeeding than employed mothers in urban Indonesia (AOR 1.587; 95% CI 1.509-1.669). The result indicated that maternal unemployment was a protective factor for the early initiation of breastfeeding in urban Indonesia. Moreover, the results also found that eight control variables were significantly correlated with the early initiation of breastfeeding: current maternal marital status, maternal age, maternal education level, parity, wealth status, antenatal care, place of delivery, and mode of delivery. Conclusion: The study found that maternal employment status correlates with the early initiation of breastfeeding in urban Indonesia. Maternal unemployment status was more likely to experience early initiation of breastfeeding than employed mothers.